Nursing of a Non-Hodgkin's Lymphoma Patient with a Facial Malignant Fungating Wound - Miaoning You; Shiyi Zhang; Xiaoxiao Ma; Huimin Liu; Yuhan Lu; Yue Li (Elsevier, 2021)
Malignant fungating wounds are severe skin lesions caused by any primary tumor, causing patient suffering and disturbing their family members. In this article, we summarize the experience of nursing a patient with non-Hodgkin's lymphoma complicated with a facial malignant wound. Initially, a chemotherapy regimen was formulated as the main treatment for the patient. Throughout the patient's treatment course, we evaluated the patient holistically, conducting debridement, anti-infection, and drainage management under the guidance of moist wound healing. Throughout the entire process, psychological nursing and health education were provided to the patient and family. Eventually, the patient's wound symptoms were well controlled, and the wound healed completely.